Procyanidins from Cranberry Press Residues—Extraction Optimization, Purification and Characterization - Linards Klavins; Ingus Perkons; Marcis Mezulis; Arturs Viksna; Maris Klavins (Plants, 2022)
Procyanidins are a polyphenolic group that can be found in a variety of foods such as chocolate, tea, cranberries and others. Type A procyanidins can be found in a handful of sources and one of the richest sources are American cranberries. These compounds possess antioxidative, anticancer and anti-inflammatory activities and are most widely used as prevention for urinary tract infections. Cranberries are utilized for jam and juice production, and the latter produces industrial food waste press residues. Press residues contain free and bound procyanidins which can be extracted for use as nutraceuticals. In this study, the extraction of cranberry press residues has been optimized using RSM and the resulting extracts have been purified and fractionated. The obtained procyanidin fractions have been investigated for their antioxidative potential and analyzed using LC-ESI-FTICR-HRMS to determine individual procyanidins. The optimization showed that the optimal extraction can be conducted using acetone in a concentration of 53% without the addition of an acidifying agent. Strong correlation was observed for procyanidin contents and their antioxidative activity using DPPH, ABTS and FRAP methods. The purified fractions contained 78 individual (65 Type A) procyanidins with the degree of polymerization of up to 9.